A new species of Hoplias (Characiformes, Erythrinidae) from the Maranhão State, western Northeast Atlantic basin, Brazil - Karen L. A. Guimarães; Juan J. Rosso; Mariano González-Castro; Sarah J. do Nascimento Andrade; Pâmella S. Brito; Erick C. Guimarães; Juan M. Díaz de Astarloa; Luís R. R. Rodrigues (Zoosystematics and Evolution)
We describe Hoplias maranhensis, a new species within the Hoplias malabaricus species-group from Maranhão, northeastern Brazil. The new species is distinguished by a unique combination of morphological, morphometric, and osteological traits, including 14–16 predorsal scales, 37–40 lateral-line scales, 39–40 vertebrae, a straight line formed by the last vertical series of scales at the base of the caudal-fin rays, and a marked ridge on the posterior angular end of the ascending process of the premaxilla. Osteologically, H. maranhensis presents the first proximal pterygiophore of the dorsal fin widely bifurcated in a “V”-shaped configuration. H. maranhensis also exhibits differences in the articulation pattern of principal caudal-fin rays with lower hypural bones, and postcleithrum 1 exhibits an anterior expansion that is in contact or nearly in contact with postcleithrum 2. The number of predorsal scales (14–16) differentiates H. maranhensis from H. argentinensis (17–19), H. microlepis (17–19), and H. teres (18). Likewise, the lateral-line scale count (37–40) and vertebrae count (39–40) distinguish the new species from H. argentinensis (41–44; 42–43), H. teres (40–41; 42), H. microlepis (43–46; 42–43), and H. mbigua (41–44; 42). Morphometric traits, such as interlandmark distances 3–5, 1–3, 2–3, 7–10, 8–10, and 9–10, further differentiate H. maranhensis from other species in the group. Genetic analysis based on DNA barcoding revealed close affinity with H. malabaricus and H. auri (3.0% divergence), followed by H. mbigua (6.0%) and H. microlepis (7.0%). Among the H. malabaricus species-group, the most divergent taxa were H. misionera and H. argentinensis (9.0%). This integrative taxonomic approach supports the recognition of H. maranhensis as a distinct taxon.